Bioactive glass: A multifunctional delivery system - Gupta S.; Majumdar S.; Krishnamurthy S. (My University, 2025)
Bioactive glasses (BAGs) were invented five decades ago and have been widely used clinically in orthopedic and stomatology. However, in the past two decades, BAGs have been explored immensely by several researchers worldwide as a multifunctional delivery system for a multitude of therapeutics ranging from metal ions to small molecules (e.g., drugs) and macromolecules (e.g., DNA). The impetus for devising a BAG-based delivery system in the 21st century is based upon the facilitative properties it offers for entrapment of a wide range of therapeutic molecules and the tailorable controlled release kinetics to the target tissue site along with the biological activity of the ionic dissolution products in several pathological conditions such as osteoporosis, cancer, infection, and inflammation. This review comprises two parts: the first part discusses the need for a new delivery system and how the journey from melt quench progressed towards template-based sol-gel mesoporous. In the second part, we have comprehended the scientific advancements made so far, emphasizing BAGs as a delivery system ranging from therapeutic ions to phytopharmaceuticals. We have also highlighted a few loopholes that have prevented bench-to-bedside clinical translation of a plethora of elucidative researches done so far. © 2021 Elsevier B.V.